KONSEP AL-TA‘JIL DAN AL-TA’KHIR DALAM PELAKSANAAN HUKUM SYARAK - Hassan, Nazrul; Sulong, Jasni (Jurnal Syariah, 2009)
Islam is a way of life that is a perfect match to abilities of human beings. Allah the Almighty knows every aspect of human beings as He is the Creator. Most of Allah’s commandments come in a general form of either to do or not to do a task. Humans often misunderstand the task until it seems too difficult resulting in delay or incorrect execution. The order of Allah must be understood well to assure every task given is accomplished in proper manner. Thus, these kind of commands need to be clarified as to be performed immediately (al-ta‘jil) or delay is acceptable (al-ta’khir). Muslims’ scholars have insights into these matters and they had weighted the situation under few conditions and priorities. To achieve these objectives, the study will look into verses from Quran and commandments of the Prophet to provide deeper insight and guide to accurate finding. Allah always comforts us and He desires for us harmony not hardship, despite formidable difficulties that we may sometimes face. It is important to raise out to the command of Allah, and know that He is always thinking highly of human potential to fulfill his commandment.